Evaluación de trichoderma spp, nativo y comercial a diferentes concentraciones en el cultivo de lechuga (lactuca sativa L.); variedad batavia; en la terrazas del Campus Salache - Cotopaxi, 2022-2023. - Arequipa Tandalla, Alison Lenin (2023)
The present research work was carried out on the terraces farming in Salache campus, Technical University of Cotopaxi. With the purpose of evaluating and determining the effect of strains of Trichoderma spp. (native and commercial) to identify the best concentration in the agronomic behavior of lettuce (Lactuca sativa L.) Batavia variety, the methodology of (Guarro, 1973) was applied for the implementation of crop, (Troya & Vaca, 2014) to work in the Trichoderma spp replication laboratory. (Vélez, and others, 1997) to carry out concentrations. The experimental design implemented was a completely randomized block design (DBCA), with three replicates and a 2X3+1 factorial arrangement, one control per replicate, the factors under study were Trichoderma spp), (native and commercial) and three concentrations 〖10〗^8, 〖10〗^9, 〖10〗^10; resulting in 21 experimental units. The variables to be evaluated were height (cm), number of leaves, width of leaves (cm), length of leaves (cm) and yield (kg/m2). For the statistical analysis, the infoStat software was used. The results achieved for T3 height variable (commercial Trichoderma spp), at the 〖10〗^10 concentration) had the best result with 9.94 cm, for the variable number of leaves T3 treatment (commercial Trichoderma spp), at the 〖10〗^10 concentration) the best result was presented with 13.03 cm, the variable width of the leaves T6 treatment (Trichoderma spp), native at the concentration 〖10〗^10) the best result was obtained with 11.42 cm to the variable length of leaves T6 treatment (Trichoderma spp), native at concentration 〖10〗^10) the best result was achieved with 11.40 cm, to the performance variable, the best result was treatment T6 (Trichoderma spp), native at concentration 〖10〗^10;) with 5.73 kg/m2 . It is concluded that the best concentration of Trichoderma spp, native and commercial was the concentration 〖10〗^10.